Spawning site selection by European anchovy (Engraulis encrasicolus) in relation to oceanographic conditions in the Strait of Sicily. (4th March 2013) - Basilone, G.; Bonanno, A.; Patti, B.; Mazzola, S.; Barra, M.; Cuttitta, A.; McBride, R.
Abstract European anchovy egg occurrence and density data from summer surveys (1998–2007) and oceanographic data were examined to study the mechanisms that control the spatial distribution of anchovy spawning habitat in the Strait of Sicily. Quotient analysis indicated habitat preference for temperature (18–19°C), bottom depth (50–100 m), water column stability (13–14 cycle h−1), fluorescence (0.10–0.15 μg m−3 Chl a), salinity (37.5–37.6 PSU), current speed (0.20–0.25 m s−1) and density (26.7–26.8 kg m−3, σt). Canonical discriminant analysis identified temperature, column stability and fluorescence as major drivers of anchovy spawning habitat. Three of the 4 years which had lower egg abundance were warmer years, with low values of primary productivity. A geostrophic current flowing through the Strait (the Atlantic Ionic Stream, AIS) was confirmed as the main source of environmental variability in structuring the anchovy spawning ground by its influence on both the oceanography and distribution of anchovy eggs. This 10‐yr data series demonstrates recurrent but also variable patterns of oceanographic flows and egg distribution. A lack of freshwater flow in this area appears to depress productivity in the region, but certain and variable combinations of environmental conditions can elevate production in some sub‐areas in most years or other sub‐areas in fewer years. These temporal and spatial patterns are consistent with an ocean triad theory postulating that processes of oceanographic enrichment, concentration, and retention may help predict fishery yields.